EFEKTIVITAS SENYAWA NONATSIRI DARI Curcuma spp. TERHADAP PENEKANAN PENYAKIT ANTRAKNOSA PADA BUAH CABAI - Anella Retna Kumala Sari; Firdaus Auliya Rahmah; Syamsuddin Djauhari (Buletin Penelitian Tanaman Rempah dan Obat, 2020)
One of the important diseases on chili is anthracnose caused by Colletotrichum capsici. Curcuma extracts and their essential oils were known as antifungal, but nonessential compounds have not been widely tested. This study aimed to assay the effectiveness of nonessential compounds of Curcuma longa, C. zedoaria, and C. aeruginosa to C. annuum. This study was conducted in November 2014 until Mei 2015 at Brawijaya University. The nonessential compound was obtained by soaking rhizome of C. longa,   C.   zedoaria,  and C.   aeruginosa in methanol, then distilled byusing rotary vacuum evaporator. Nonessential chemical compunds were identified by using HPLC. Effectiveness evaluation of nonessential compounds from three species of Curcuma was done by in vitro and in vivo test. Tested treatments were three species of Curcuma spp and 6 concentration levels of nonessential compounds (0 ppm, 4 ppm, 6 ppm, 8 ppm, 10 ppm, and 12 ppm). The xperiment was performed in Factorial Complete Randomized Design, with 18 treatments combination, and replicated three times. Results of HPLC analysis showed the rhizomes of the three Curcuma species contained curcumin and desmethoxycurcumin in various concentrations. The highest level was found in the C. longa extract (13.792 ppm curcumin and 67.156 ppm desmethoxycurcumin). However, in vitro test results showed nonessential compound of C. zedoaria was most effective in inhibiting C. annuum growth.  The 10 ppm concentration inhibited 81.53 % of fungal growth.  Further, the in vivo test, also indicated the same, it’s most effective in hampering the growth of anthracnose symptoms. Therefore, curcumin and desmethoxycurcumin from three species of Curcuma have potential to be developed as botanical fungicide.